Мурли: [сказочная повесть] / Анни Шмидт - Шмидт Анни Мария Гертруда (Школьная библиотека, 2006)
Экземпляры: С/а ДБ (20100319) / Инвентарный номер: 95936 / Цена: 40.00 / Авт.знак: Ш 73 / ГРНТИ: 17.82 / ББК: 84(4Нид)